Effect of bedside filtration on aggregates from cold‐stored whole blood–derived platelet‐rich plasma and apheresis platelet concentrates. Issue 1 (15th November 2021) - Li, Valery J.; Bailey, S. Lawrence; Miles, Jeffrey; Usaneerungrueng, Chomkan; Fang, Lydia Y.; Corson, Jill; Osborne, Barbara; Özpolat, Tahsin; López, José A.; Wu, Yanyun; Stolla, Moritz
Abstract: Background: The current approach to manufacture cold‐stored platelets (CSP) replicates that of room temperature–stored platelets (RSP). However, this production method is associated with aggregate formation in CSP, a major pitfall that leads to significant wastage. We hypothesized that isolating platelets from whole blood as platelet‐rich plasma (PRP) and storing them at a lower concentration reduces aggregates and that conventional bedside transfusion filtration removes CSP aggregates. Methods: We collected platelets from healthy humans by apheresis (AP) and by phlebotomy, from which we generated platelet‐rich plasma (PRP). We split each AP and PRP platelets into two equal aliquots, storing one at 22°C (RT‐PRP and RT‐AP) and the other at 4°C (4C‐PRP and 4C‐AP). We evaluated platelets on day 0 and day 7 of storage. After storage, we measured platelet counts, aggregates, and other key characteristics before and after filtration by a bedside filter. Results: After storage, the 4C‐AP platelet counts decreased significantly. 4C‐PRP preserved glucose better and prevented a significant increase in lactate contrary to 4C‐AP. Filtration led to significantly lower platelet counts in both 4C‐PRP and 4C‐AP but not in their RT counterparts. Post filtration, we observed 50% fewer aggregates only in 4C‐AP, whereas 4C‐PRP showed an unexpected but significant increase in aggregates. Testing confirmed activation during storage but filtration did not further activate platelets. Conclusion: We provide evidence that 4C‐PRP is an alternative to 4C‐AP and that bedside filters reduce aggregates from 4C‐AP. Further studies are needed to evaluate the hemostatic potential of 4C‐PRP and the management of aggregates.